2014
DOI: 10.1259/bjr.20140145
|View full text |Cite
|
Sign up to set email alerts
|

The value of pre-operative multicompartment pelvic floor ultrasonography: a 1-year prospective study

Abstract: Objective: Comprehensive assessment of the pelvic floor (PF) provides information and diagnoses of coexisting abnormalities that may affect operative decisions. Our aim was to establish if pre-operative PF ultrasonography (PFUS) in patients complaining of PF dysfunction can complement clinical findings and contribute to additional management strategies. Methods: Females were recruited from the urogynaecology/ gynaecology clinics between July and October 2009 and underwent pelvic organ prolapse quantification (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…5,6 A recent publication demonstrated that the coexisting abnormalities identified on ultrasound do not change the initial surgical management or the management at 1-year follow-up. 14 Clinicians and researchers are increasingly using PFUS as part of the work-up of PFD; 1,5-7,17 therefore, it is important to assess the interobserver agreement of pelvic floor anatomical measurements using multicompartment PFUS. In order to determine the relevant clinical application of PFUS, long-term studies are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 A recent publication demonstrated that the coexisting abnormalities identified on ultrasound do not change the initial surgical management or the management at 1-year follow-up. 14 Clinicians and researchers are increasingly using PFUS as part of the work-up of PFD; 1,5-7,17 therefore, it is important to assess the interobserver agreement of pelvic floor anatomical measurements using multicompartment PFUS. In order to determine the relevant clinical application of PFUS, long-term studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This study population also formed a part of another study evaluating the value of pre-operative multicompartment PFUS. 14 Prior to the examination, patients were asked to empty their bladder if it was felt full or uncomfortable. POPQ assessment was conducted by an independent examiner (either RT or AHS) in the left lateral and standing position as per unit protocol and examination was completed using bimanual pelvic palpation.…”
Section: Ethics Approvalmentioning
confidence: 99%
“…All patients underwent vaginal examination performed by experienced clinicians (AHS, RT). This study population also forms part of another study from our group evaluating the value of pre-operative multicompartment pelvic floor ultrasonography [9].…”
Section: Methodsmentioning
confidence: 99%
“…High-frequency endovaginal ultrasound eliminates the limitations of TPUS and has been reported to be a reliable tool in the assessment of vascularity of nulliparous female urethra [6,7] owing to the small array of the transducer, high-frequency (9)(10)(11)(12) and direct contact of the transducer and the organs examined, providing high resolution and resulting in more precise visualisation of the urethra. These features make EVUS highly efficient in the assessment of the urethral vascularity pattern, even including the smallest vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Integrated total pelvic floor ultrasound is becoming the standard of care, along with the multidisciplinary team approach to the evaluation and treatment of pelvic floor dysfunction [20][21][22].…”
mentioning
confidence: 99%